Boosting Employee Performance through Culture, Compensation, and Motivation in Indonesia - Rani Rahmawati; Hasan Ubaidillah (Universitas Muhammadiyah Sidoarjo, 2024)
In the context of today's advanced economic development, companies aim to create jobs and improve the economy. This study examines the influence of organizational culture, compensation, and work motivation on employee performance at PT. Romi Violeta, a furniture company. Despite extensive research on employee performance determinants, the specific impacts of these factors within the Indonesian furniture industry remain underexplored. This study addresses this gap by utilizing a quantitative method with a sample of 133 employees selected through purposive sampling. Data analysis was performed using multiple linear regression with SPSS version 22. The findings reveal that organizational culture, compensation, and work motivation each positively affect employee performance. Furthermore, when considered together, these factors significantly enhance employee performance. Among them, compensation is the most dominant factor due to the substantial impact of adequate wages on optimizing employee performance. These results suggest that fostering a strong organizational culture, providing fair compensation, and enhancing work motivation are crucial strategies for improving employee performance in similar industrial contexts. Highlight: Positive Impacts: Organizational culture enhances employee performance. Dominant Factor: Compensation most influences employee performance. Combined Effect: Culture, compensation, and motivation jointly boost performance. Keywoard: Organizational Culture, Compensation, Work Motivation, Employee Performance, Quantitative Analysis